Assistance in the Management of the Taklim Assembly Al Mukhlisin Mosque Air Bang, Curup Tengah, Rejang Lebong - Syaiful Bahri; Jumira Warlizasusi; Mardian Effendi (Asosiasi Profesi Multimedia Indonesia, 2024)
This community service was motivated by the activities of the Taklim Assembly at the Al-Mukhlisin Mosque which is located on Jl. Bhakti Osis 1, Air Bang Curup Tengah Subdistrict, for the past 5 years has not been actively carrying out its functions and activities so that there is no communication and friendship between administrators, especially with the national Covid-19 outbreak (several administrators have died). The aim of this activity is to provide administrative management assistance to the Al-Mukhlisin Mosque Taklim Assembly. The results of the activities included that the Al-Mukhlisin Mosque Taklim Assembly management was able to understand and create agenda books for incoming and outgoing letters, create AD and ART, make proposals for the permit registration process and obtain statistical numbers from the Ministry of Religion of Rejang Lebong Regency, make submissions or requests to study presenters, make a letter expedition book, make notes in the general cash book of the Taklim Assembly, make reports on the implementation of the Taklim Assembly's activities, take attendance of administrators and congregations as well as other taklim assembly activities, make draft speeches and opening remarks, make arrangements and series of activities of the Taklim Assembly and other activities, make books and notes on meeting minutes, creating a schedule for the Taklim Assembly's activities and management activities. So, it can be concluded that administrative management assistance provides understanding and a sense of enthusiasm for the administrators and members of the Taklim Assembly in carrying out the administrative management of the Al-Mukhlisin Mosque.